2020
DOI: 10.3390/biom10060849
|View full text |Cite
|
Sign up to set email alerts
|

A Ribosome Interaction Surface Sensitive to mRNA GCN Periodicity

Abstract: A longstanding challenge is to understand how ribosomes parse mRNA open reading frames (ORFs). Significantly, GCN codons are over-represented in the initial codons of ORFs of prokaryote and eukaryote mRNAs. We describe a ribosome rRNA-protein surface that interacts with an mRNA GCN codon when next in line for the ribosome A-site. The interaction surface is comprised of the edges of two stacked rRNA bases: the Watson–Crick edge of 16S/18S rRNA C1054 and the adjacent Hoogsteen edge of A1196 (Escherichia coli 16S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…A key aspect of CAR function is that the interaction between CAR and the +1 codon is sensitive to the sequence at the +1 codon. Using N1, we showed previously that GCU at the +1 codon leads to strong CAR/+1 codon interactions, whereas replacement of the second nucleotide (GGU, GAU or GUU) led to significantly reduced interactions [12]. The same relationship was observed with N2 ( Figure S5) confirming our previous conclusion that the CAR interaction is sequence sensitive with a preference for GCN codons, and suggesting that sensitivity to translation regulation through the CAR interface likely depends on the degree to which codons in a gene's ORF conform to GCN.…”
Section: Ribosome Subsystems Provide Neighborhoods For Molecular Dynamentioning
confidence: 93%
See 4 more Smart Citations
“…A key aspect of CAR function is that the interaction between CAR and the +1 codon is sensitive to the sequence at the +1 codon. Using N1, we showed previously that GCU at the +1 codon leads to strong CAR/+1 codon interactions, whereas replacement of the second nucleotide (GGU, GAU or GUU) led to significantly reduced interactions [12]. The same relationship was observed with N2 ( Figure S5) confirming our previous conclusion that the CAR interaction is sequence sensitive with a preference for GCN codons, and suggesting that sensitivity to translation regulation through the CAR interface likely depends on the degree to which codons in a gene's ORF conform to GCN.…”
Section: Ribosome Subsystems Provide Neighborhoods For Molecular Dynamentioning
confidence: 93%
“…Modulation of these interactions provides potential pathways for fine-tuning rates of protein translation in different cellular conditions. Cryo-EM studies in yeast have identified five intermediate stages of ribosome translocation (stages I through V; [17]) and we have identified a ribosome interaction surface, named CAR [12,18], that has pronounced hydrogen-bonding to the mRNA during the early translocation stages I and II. CAR interacts with the +1 codon next in line to enter the ribosome A site.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations